1994
DOI: 10.1016/0378-7753(94)87016-0
|View full text |Cite
|
Sign up to set email alerts
|

Advances in direct oxidation methanol fuel cells

Abstract: Fuel cells that can operate directly on fuels such as methanol are attractive for low to medium power applications in view of their low weight and volume relative to other power sources.A liquid feed direct methanol fuel cell has been developed based on a proton exchange membrane electrolyte and Pt/Ru and Pt catalyzed fuel and air/O2 electrodes respectively.The cell has been shown to deliver significant power outputs at temperatures of 60 to 90* C. The cell voltage is near 0.5 V at 300 mA/cm 2 current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(128 citation statements)
references
References 3 publications
1
126
1
Order By: Relevance
“…Besides its utilization in ICEs, methanol is an excellent fuel for efficient direct methanol fuel cells (DMFC), which we jointly developed with Caltech's Jet Propulsion Laboratory in the early 1990s. [27][28][29] Direct DME based fuel cells are also being studied. 30,31 Methanol and DME, besides their use as transportation fuels, are proven and increasingly utilized starting materials for producing ethylene and propylene in the so-called methanol to olefin (MTO) process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its utilization in ICEs, methanol is an excellent fuel for efficient direct methanol fuel cells (DMFC), which we jointly developed with Caltech's Jet Propulsion Laboratory in the early 1990s. [27][28][29] Direct DME based fuel cells are also being studied. 30,31 Methanol and DME, besides their use as transportation fuels, are proven and increasingly utilized starting materials for producing ethylene and propylene in the so-called methanol to olefin (MTO) process.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known PtRu catalyst is effective as an anode material. [5][6][7][8][9][10] However, both Pt and Ru are expensive, leaving room for development of active but cheaper electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It has been reported that even over 40% of methanol could be lost in a DMFC due to crossover across the membrane.…”
mentioning
confidence: 99%
“…3 However, the methanol crossover from anode to cathode across the Nafion membrane brings about a mixed potential at the cathode causing both the loss of fuel and cell polarization impeding their commercial realization. [4][5][6] It has been reported that even over 40% of methanol could be lost in a DMFC due to crossover across the membrane. 7 Methanol crossover across the Nafion membrane can be kept to a minimum by controlling the methanol-feed concentration.…”
mentioning
confidence: 99%